Aspects of Kinship in Ancient Iran - Potts, D. T. (University of California Press, 2023)
Originally delivered in 2020 as the Biennial Ehsan Yarshater Lectures, Aspects of Kinship in Ancient Iran is an exploration of kinship in the archaeological and historical record of Iran's most ancient civilizations. D. T. Potts brings together history, archaeology, and social anthropology to provide an overview of what we can know about the kith and kinship ties in Iran, from prehistory to Elamite, Achaemenid, and Sasanian times. In so doing, he sheds light on the rich body of evidence that exists for kin relations in Iran, a topic that has too often been ignored in the study of the ancient world. "As always with this excellent authority on ancient Iranian history and cultures, D. T. Potts presents five highly innovative essays on forms of kinship and social organization in ancient Iran from the Elamites to the Sasanians that are full of new ideas and suggestions for further research." - Josef Wiesehöfer, Professor Emeritus of Ancient History and Classics, University of Kiel, and author of Ancient Persia: From 550 BC to 650 AD